2004
DOI: 10.1371/journal.pbio.0020294
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Muscle Fiber Type and Running Endurance by PPARδ

Abstract: Endurance exercise training can promote an adaptive muscle fiber transformation and an increase of mitochondrial biogenesis by triggering scripted changes in gene expression. However, no transcription factor has yet been identified that can direct this process. We describe the engineering of a mouse capable of continuous running of up to twice the distance of a wild-type littermate. This was achieved by targeted expression of an activated form of peroxisome proliferator-activated receptor δ (PPARδ) in skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

58
1,061
7
17

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 985 publications
(1,143 citation statements)
references
References 28 publications
58
1,061
7
17
Order By: Relevance
“…In recent years PPARδ has emerged as a key protein in the regulation of energy metabolism by its ability to enhance fatty acid catabolism, energy uncoupling and insulin sensitivity in the liver, adipose tissue and skeletal muscle [6][7][8][9][10]36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years PPARδ has emerged as a key protein in the regulation of energy metabolism by its ability to enhance fatty acid catabolism, energy uncoupling and insulin sensitivity in the liver, adipose tissue and skeletal muscle [6][7][8][9][10]36].…”
Section: Discussionmentioning
confidence: 99%
“…PPARδ acts as a regulator of fatty acid β-oxidation in both adipose tissue and skeletal muscle. In skeletal muscle, overexpression of Ppard in mice increases oxidative metabolism, changes muscle fibre type towards oxidative type I fibres and improves physical endurance thereby averting obesity induced by a high-fat diet or genetically [6,7]. Additionally, a recent study of genetically modified mice provides evidence that PPARδ regulates glucose metabolism and insulin sensitivity in both skeletal muscle and the liver, interestingly indicating a subtle PPARδ-controlled change in substrate utilisation [8].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of PPAR-δ on fuel metabolism are attributed to the increased expression of genes involved in lipid metabolism, uncoupling of oxidative phosphorylation, and mitochondrial biogenesis, which leads to elevated energy expenditure and fat dissipation [4,5,8,9]. In this context, the quantitatively most important target organ seems to be skeletal muscle, which makes a major contribution to whole-body fuel oxidation and expresses PPAR-δ more abundantly than other PPAR subtypes [10].…”
mentioning
confidence: 99%
“…In this context, the quantitatively most important target organ seems to be skeletal muscle, which makes a major contribution to whole-body fuel oxidation and expresses PPAR-δ more abundantly than other PPAR subtypes [10]. Accordingly, targeted overexpression of PPAR-δ in mouse skeletal muscle distinctly elevates the number of red type-1-like fibres, characterised by high mitochondrial density and oxidative capacity [9,11]. Furthermore, several studies have consistently shown that agonists of PPAR-δ markedly increase the rate of fatty acid oxidation by specimens of skeletal muscle both ex vivo and in vitro [4,5,10].…”
mentioning
confidence: 99%
“…PPARβ/δ agonist treatment of diabetic db/db, ob/ob or high fat-fed mice reduces weight gain, increases skeletal muscle fatty acid oxidation and decreases plasma triglycerides 31,51,52 . In line with these previous data, our results show that GW501516-treated ob/ob mice also displayed a 10% decrease of body weight in association with a reduction of epididymal adipocyte tissue mass (2.7±0.1 vs. i n s u p e r n a t a n t P P A R β / δ a g o n i s t t r e a t m e n t RNA quantification by real-time PCR.…”
Section: Han Et Al Recently Demonstrated That Thementioning
confidence: 99%